Fungal disease cluster in tropical terrestrial frogs predicted by low rainfall. (September 2021) - Moura-Campos, Diego; Greenspan, Sasha E.; DiRenzo, Graziella V.; Neely, Wesley J.; Toledo, Luís Felipe; Becker, C. Guilherme
Abstract: Anthropogenic forces are increasing climate anomalies and disease pressure in tropical forests. Terrestrial-breeding amphibians, a diverse group of highly endemic tropical frogs, have been experiencing cryptic population declines and extinctions, most of which have been retrospectively linked to climate anomalies and the fungal pathogen Batrachochytrium dendrobatidis (Bd). However, the spatiotemporal drivers of Bd infection in these species are unresolved. We tracked microhabitat conditions and Bd dynamics in terrestrial-breeding frogs in Brazil's Atlantic Forest over an annual cycle that coincided with a period of low rainfall compared to historical averages. An increase in Bd prevalence during the warm/wet season was attributable to pathogen spillover from co-occurring aquatic-breeding frogs. The deficit in rainfall compared to historical trends was the best predictor of spikes in Bd infection loads one month later and mortality among heavily infected frogs two months later. We suggest that hydrological stress may intensify seasonal pathogen amplification in direct-developing frogs, to an extent that may trigger localized disease clusters or potentially shift disease dynamics from enzootic to epizootic, even in areas with a relatively long history of host-pathogen coexistence. Highlights: Tropical terrestrial-breeding frogs are declining from the disease chytridiomycosis. We tracked spatiotemporal drivers of infection in Brazilian terrestrial frogs. Drought was the best predictor of increased host infection loads and mortality. Our study includes the first real-time report of chytridiomycosis in the wild in Brazil. Increasing drought stress under global change may amplify frog disease risk.